Somatosensory-Evoked Potentials and Clinical Assessments of Sensory Function Over Time in Patients With Subacute Stroke - Hiroshi Fuseya; Syoichi Tashiro; Osamu Takahashi; Yukiko Kobayashi; Tetsuya Tsuji; Katsuhiro Mizuno (Neural Plasticity)
Conclusion: Despite the limitations of the retrospective study design, our study highlights the utility of SEPs for evaluating sensory function in patients with subacute stroke, setting the foundation for further investigations on the use of SEPs to assess functional changes in patients with subacute stroke undergoing rehabilitation.